2006
DOI: 10.1007/s00125-006-0328-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in patient weight and the impact of antidiabetic therapy during the first 5 years after diagnosis of diabetes mellitus

Abstract: Aims/hypothesis It is generally thought difficult for type 2 diabetic patients to lose weight. We monitored changes in patients' weight during the first 5 years after diabetes diagnosis in relation to initiation of antidiabetic treatment. Subjects and methods Data from 711 newly diagnosed diabetic patients aged 40 or over were analysed with a random-effect linear-regression model. Patients were included consecutively from a well-defined patient list in general practice. Results In 245 patients whose only treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…Prior studies have pointed out that anti-hyperglycemic therapies, 6 duration of diabetes, 5 and sex 7 may affect weight change in diabetes patients; results from the present study support and extend previous findings. The weight cumulating morbidly obese group was disproportionately female, members of minority groups, as well as reporting greater comorbid health conditions and being treated with insulin, Table 2 of the supplemental appendix on line.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Prior studies have pointed out that anti-hyperglycemic therapies, 6 duration of diabetes, 5 and sex 7 may affect weight change in diabetes patients; results from the present study support and extend previous findings. The weight cumulating morbidly obese group was disproportionately female, members of minority groups, as well as reporting greater comorbid health conditions and being treated with insulin, Table 2 of the supplemental appendix on line.…”
Section: Discussionsupporting
confidence: 90%
“…Research in clinical and community settings has examined general weight change patterns in adults living with diabetes over time, yielding inconsistent findings [2][3][4][5][6][7] and suggesting that the longitudinal course of body weight in middle-aged and older adults with diabetes exhibits not only intra-individual but also inter-individual variation.…”
mentioning
confidence: 99%
“…De Fine Olivarius et al 168 reported that 330 patients did not gain weight after starting on sulfonylureas. They make the point that most patients with type 2 diabetes are treated in primary care and are seldom recruited to trials, and that trials may therefore not be generalisable to all patients.…”
Section: Problems With Evidence and Effect Sizes For Modellingmentioning
confidence: 99%
“…Oral antidiabetics, incretin-based therapies, and insulin have effects on lipid measurements which differ within and between classes of agents [18]. Furthermore, antidiabetic therapy may have an effect on weight in type 2 diabetes; for example, sulfonylureas or insulin are associated with weight gain while metformin is associated with weight stabilization or weight loss [19]. However, one study of 245 newly diagnosed diabetics who received dietary counseling found that patients did not have a weight change when treatment with sulfonylureas or metformin was begun [19].…”
Section: Discussionmentioning
confidence: 99%